Longitudinal investigation of interpersonal trauma exposure and alcohol use trajectories. (February 2016) - Berenz, Erin C.; Cho, Seung Bin; Overstreet, Cassie; Kendler, Kenneth; Amstadter, Ananda B.; Dick, Danielle M.
Abstract: Background: The current longitudinal study examined associations between interpersonal potentially traumatic events (PTEs; i.e., sexual or physical assault) and changes in alcohol consumption among incoming college students. Methods: 1197 students (68% female) participating in a university-wide research study were included in analyses. Assessments were administered at three time-points and included measures of alcohol use, PTEs (Life Events Checklist), and a screener for possible PTSD symptoms (abbreviated Primary Care PTSD Screen). Linear growth curve models were fit to the three repeated measures of alcohol quantity and frequency to determine the role of pre-college and college-onset interpersonal PTEs and possible PTSD symptoms on patterns of alcohol use. Results: Pre-college interpersonal PTE was associated with greater baseline alcohol use for female but not male students. College-onset interpersonal PTE predicted greater alcohol use at concurrent and future assessments for women but not men, beyond the effects of pre-college PTE. Pre-college possible PTSD symptoms did not predict baseline or change in alcohol use. Conclusions: There may be a stronger and longer-lasting impact of interpersonal PTE for college women compared to men on alcohol phenotypes, although replication in studies oversampling men endorsing interpersonal PTE is needed. Highlights: Pre-college interpersonal trauma predicts greater first semester alcohol use for female students. College-onset interpersonal trauma predicts greater concurrent and future alcohol consumption for female students. Associations between interpersonal trauma and alcohol use may be more salient for women than men. Almost a quarter of college women endorsed interpersonal trauma during the first two years of college.